Compensation of London Dispersion in the Gas Phase and in Aprotic Solvents. (30th August 2019) - Pollice, Robert; Fleckenstein, Felix; Shenderovich, Ilya; Chen, Peter
Abstract: The importance of London dispersion for structure and stability of molecules with less than about 200 atoms has been established in recent years but the quantitative understanding is still largely based on computations because of a persistent lack of suitable experimental data. We herein report a comprehensive computational and experimental study of the compensation of London dispersion in proton‐bound dimer dissociations showing that total compensation is largely invariant in both polar and nonpolar aprotic solvents spanning a wide range of bulk polarizabilities. Additionally, we find that compensation by solvent (which is about 40–80 %) largely dominates over compensation in the gas phase (which is about 0–40 %) for typical experimental temperatures. Abstract : Quid pro quo : London‐Dispersionskräfte werden in Lösung, im Vergleich zur Gasphase bei 0 K, signifikant kompensiert. Bei Umgebungstemperaturen stammt der Großteil der Gesamtkompensation von Solvatisierung, während die Gasphasenentropie einen deutlich geringeren, aber doch wichtigen Anteil ausmacht. Die Gesamtkompensation ist weitestgehend unabhängig von der Polarisierbarkeit des Lösungsmittels.